THE MARKETING STRATEGY OF SMALL AND MEDIUM ENTERPRISES PRODUCTS THROUGH LANGUAGE LITERACY IN KALANGANYAR TOURISM VILLAGE - Elli Setiyo Wahyuni (Universitas Tribhuwana Tungga Dewi, 2022)
Marketing language literacy is a communication skill that must be mastered by business people in Kalanganyar tourist village. UMKM business from processed fish becomes a product that can have high competitiveness if it has a good marketing method to consumers. Kalanganyar tourism village is a fostered area or cooperation partner who will implement an international standard tourist village and language literacy is the answer to the problems of people who do not master this marketing language literacy. Community service in the tourist village of Kalanganyar aims to create a community of business people who can practice the language of communication in English in sales and purchasing activities. In addition, knowledge of an effective marketing system is given to business people to equip the community in marketing processed products online and offline with special language literacy, namely marketing English. With the strengthening of language literacy and a reliable marketing system, the vision and mission of an international tourist village can be realized gradually and is expected to encourage Kalanganyar community to realize the tourism village program.